Comparing the Behavior and Growth of Red and Black Tilapia in the Same Pond - Margolang, Anggi R.; Nasution, Tulus I.; Wahyuningsih, Hesti; Matondang, Aprima A.; Yohana, Winda Y. (Journal of Applied Geospatial Information, 2024)
This study compared the growth of red and black tilapia in a shared pond. It examined environmental factors, including temperature, pH levels, dissolved oxygen (DO), and total dissolved solids (TDS). The study employed a solitary water pump system to monitor fish growth and water quality over 36 days. Although there was a decline in dissolved oxygen (DO) levels on day 18, red tilapia exhibited accelerated growth and higher survival rates, suggesting enhanced environmental adaption compared to black tilapia. The feeding parameters were of utmost importance, and Prima Feed (PF 1000) performed a critical role by offering the ideal levels of protein (39-41%), fat (5%), fiber (6%), ash (16%), and water content (10%). Water quality assessments indicated varying dissolved oxygen (DO) levels, which were affected by temperature fluctuations caused by unpredictable weather conditions. Although the TDS range of 0.5-1.0 ppm was deemed suitable for tilapia cultivation, the total water quality remained suboptimal throughout the investigation. However, the findings indicated that red tilapia exhibited a greater growth rate than black tilapia under identical pond conditions. This can be related to the red tilapia's improved capacity to withstand fluctuations in temperature and retain a higher level of physiological stability. This study offers significant findings regarding the disparities in the two tilapia species' behavior, growth, and survival. These findings can be used to enhance pond management and maintenance procedures to achieve better outcomes in aquaculture.